The Implementation of the Problem-Based-Learning Model Assisted by Infographic Media to Improve Fourth Grade Students' Learning Outcomes in Pancasila Education - Nurul Hasna Tobibah; Dianasari Dianasari; Diana Setiana (Journal of Educational Sciences, 2026)
The low students' learning outcomes of fourth-grade elementary school students in Civic Education, particularly on the topic of village and sub-district government, are attributed to teacher-centered instruction and the limited use of interactive learning media. This study aimed to improve students' learning outcomes through the implementation of the Problem-Based-Learning (PBL) model assisted by infographic media. The research employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, consisting of two cycles: planning, action, observation, and reflection. The study was conducted at SDN 2 Patapan involving 17 fourth-grade students. Data were collected through classroom observations, interviews, and achievement tests, and analyzed using descriptive quantitative methods. The findings revealed a significant improvement in students' learning outcomes after implementing the PBL model with infographic media. Learning mastery increased from 17% in the pre-cycle to 29% in Cycle I and reached 82% in Cycle II. The average score also improved from 54 in the pre-cycle to 60 in Cycle I and 84 in Cycle II. Furthermore, students demonstrated greater participation, enthusiasm, collaboration, and critical thinking during the learning process. Therefore, the integration of the Problem-Based-Learning model with infographic media proved effective in enhancing both the learning process and students' learning outcomes in Civic Education.